2020
DOI: 10.3390/w12102815
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity and Moisture Control the Processes of Soil Nitrification and Denitrification in a Riparian Wetlands in an Extremely Arid Regions in Northwestern China

Abstract: Soil nitrification and denitrification are key nitrogen (N) removal processes in riparian wetlands in extremely arid regions, but the driving factors of the two N processes in these wetlands are still unclear. We measured soil nitrification and denitrification rates and related environmental properties in a typical riparian wetland in the middle reaches of the Heihe River, northwestern China. Our results showed that rates of soil nitrification and denitrification exhibited moderate variability, ranging from 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The A horizon contains the highest value of OM (Table 1) which should contribute to faster water percolation and permeability [39]. Additionally, drastic reduction in soil water content can also have significant impact on the denitrification rates [88]. The same research also showed that soil nitrification can both decrease and increase depending on the soil water content.…”
Section: Factors Influencing Nomentioning
confidence: 88%
“…The A horizon contains the highest value of OM (Table 1) which should contribute to faster water percolation and permeability [39]. Additionally, drastic reduction in soil water content can also have significant impact on the denitrification rates [88]. The same research also showed that soil nitrification can both decrease and increase depending on the soil water content.…”
Section: Factors Influencing Nomentioning
confidence: 88%
“…The model developed in this study focus on human activities which cause urban expansion. Data on soil properties, which had been found by Baoshan et al [56] and Meng et al [57] to be the key predictors in the water body change were not included in the model. More detailed data, especially the topographic might be necessary to improve the model's performance as it has been found that most water body change occurs on flat slope [58].…”
Section: ) Panel Data Analysismentioning
confidence: 99%
“…Overall, it can be concluded that both soil and irrigation water salinity significantly affect the N 2 O emissions from soils. Usually, the higher the levels of salts, the lower the N 2 O emissions [26,66]. Although, soil salinity is a limiting factor affecting the nitrification and denitrification processes by changing the microbial growth and activity as well as the physical and chemical properties of soil.…”
Section: Poffenbarger Et Al [89]mentioning
confidence: 99%
“…Beside this moisture is the key factor influencing nitrification and denitrification in salt-affected soils [65]. Denitrification had a significantly positive relationship with soil moisture and it increased with an increase in soil moisture when the soil water content was less than 27.03% and decreased with an increase in soil moisture when the soil water content was more than 27.03% [66].…”
Section: Poffenbarger Et Al [89]mentioning
confidence: 99%
See 1 more Smart Citation